Reformar el código civil sustituyendo el art. 83: las personas mayores de dieciséis y menores de dieciocho, estarán facultadas para casarse cuando declaren voluntad propia expresa de forma individualizada ante la autoridad competente y previo conocimiento de quien posea su patria potestad - Morocho Romero, Luis Alonso (2016)
Teens today represent a very important group of people that make up our society, being of considerable importance for the State, since with its contingent they are becoming a bulwark for that in the further they govern the future of the nation, reason why dominating training is consistent with their rights and obligations. With this background the Ecuadorian State has made partners teens so at sixteen years of age, to acquire the right of participation promoting responsibility for choosing future leaders, recognizing them this way that have come to early maturity, making an adjuvant that Ecuadorian society which must requires them fundamental responsibilities. In the Constitution, approved in 2008, has as a fundamental characteristic of being protective of rights and in where in its relevant part refers to persons in the enjoyment of political rights, they empower sixteen years and older adolescents to exercise the right to vote of age. Despite this constitutional precept, there is disagreement with the current legal regulations, specifically I will refer to the Civil Code, where currently violates the right of adolescents to prevent that persons over sixteen years of age may enter into marriage; against this background, it is necessary that there is a legal precept that recognizes the marriage of adolescents over the age of sixteen years and younger than eighteen, already that if a teenager has the ability to choose a candidate for any dignity, also possesses the ability to distinguish and to accept the responsibilities it takes on marriage; It is also important to point out that teens over the age of 16 and persons under 18 years to comply with civil marriage must meet certain requirements, as do it voluntarily it expresses individualized to the competent authority and knowledge of the persons having their parental authority, to prevent forced marriage, by convenience or any other nature that violates their rights to many times also teens may become marriage prior to training, guidance and counseling for the effect.